The Role of Organizational Culture in Interpersonal Communication: The Mediating Role of Organizational Citizenship Behavior (OCB) among Employees in the Sports Fashion Industry - Desyantoro, Irwan; Wangge, Maria Yuliana; Katkar, Kimmy; Muhaimin, Ahmad (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
The sports fashion industry is characterized by dynamic business processes that require intensive cross-functional collaboration, rapid decision-making, and effective interpersonal communication to support organizational performance. In this context, organizational culture is considered a fundamental factor in shaping the quality of interpersonal communication among employees. Beyond its direct influence, organizational culture may also affect interpersonal communication through employees' behavioral mechanisms, particularly Organizational Citizenship Behavior (OCB), which reflects discretionary behaviors that extend beyond formal job requirements. This study aimed to examine the direct effect of organizational culture on interpersonal communication and its indirect effect through OCB as a mediating variable among employees of a sports fashion company. The study involved 110 employees of PT X, a company operating in the sports fashion industry, using a saturated sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that organizational culture had a positive and significant direct effect on interpersonal communication (β = 0.780, p < .001). Furthermore, organizational culture also exerted a significant indirect effect on interpersonal communication through OCB (β = 0.330, p < .001), indicating that OCB partially mediated the relationship between organizational culture and interpersonal communication. These findings suggest that strengthening organizational culture not only directly enhances interpersonal communication but also promotes employees' extra-role behaviors, which further improve communication effectiveness within the organization. Practically, this study highlights the importance of fostering a collaborative organizational culture that encourages Organizational Citizenship Behavior to enhance interpersonal communication, particularly in organizations operating in the sports fashion industry.